Development of Saxaul Cultivation in Uzbekistan - Fayzullayev Utkir Aminqulovich; Mamayusupova Laylo Gulom qizi (American Journal of Biology and Natural Sciences, 2025)
Among the plants, saxaul sand is better than all strengthens. Saxaul sand with strongly developed root networks ggrabs its masses and stops its course, where other plants and bushes grow and develop from trees and shrubs ggrow outside deserts the saxaul makes a sharp faq White saxaul barbed shells that are on the stems not counting (cheshuyek) they do not have leaves. For this reason organic matter in plants is fresh it accumulates on overgrown branches (like some desert plants).